Privatisation and public enterprises in India: Issues of policy and implementation - Raghavulu, C.V. (1996)
With a brief background on the basic nature of our economy and role therein and performance of PSEs, the author focusses discussion on modalities of privatisation of PSEs under the liberalisation process. Highlighting the problems in this process of privatisation, he suggests, for transparency reasons, intervention of specially created expert institutions/bodies. - Reproduced
Keywords: Liberalization - India; Privatization - India; Government business enterprises - India; Public sector; Privatization